Socio-economic impacts caused by the restoration of peatlands and small water bodies - Juutinen, Artti; Artell, Janne; Iivonen, Suvi; Tolvanen, Anne (Luonnonvarakeskus, 2024)
The restoration of peatlands and small water bodies (streams, ponds, and bird lakes) aims to restore the structure and function of these ecosystems, which have deteriorated primarily due to forestry, drainage, and eutrophication. Although restoration of peatlands and small water bodies is costly, it provides work opportunities, improved biodiversity and increased water quality, and may improve the recreational and tourism value of the area. Assessing the restoration costs in relation to the benefits and people’s opinions about restoration helps to evaluate the socio-economic impacts and acceptance of restoration. We studied the socio-economic impacts of restoration of peatlands and small water bodies through five case studies: 1) by assessing the financial costs and employment effects of restoration, 2) through a public survey focusing on citizens’ general awareness, beliefs, and attitudes towards restoration at two time occasions, 3) through a nationwide survey concerning the willingness of people to pay for the restoration of peatlands and small water bodies, 4) through a nationwide survey concerning citizens’ preferences and attitudes towards restoration in Finnish national parks, and 5) through a targeted questionnaire to the visitors of Nuuksio National Park in Southern Finland to assess how restoration would influence their visits in the national park. The studies were carried out as part of the EU funded Hydrology LIFE project (LIFE16 NAT/FI/000583) which focuses on the restoration of peatlands and small water bodies in Finland. The results show that the employment effects of the restoration can be significant if the restoration is carried out on a large scale, especially in remote areas. The public survey showed that there were no changes in knowledge or opinions towards restoration among citizens during the last five years. The majority of respondents considered that restoration of peatlands and small water bodies have positive effects on the nature and biodiversity and thus improves opportunities for recreational use. Interestingly, the respondents were ready to use more tax money for restoration. The nationwide survey showed that the potential restoration programs considered in the study provided significant benefits or welfare effects, and the annual WTP values varied from €335 to €427 per household. There was a preference for large restoration programs over small ones, peatland restoration over small water bodies, and state-owned lands over private lands, whereas the proximity of restoration sites to the respondents’ homes did not have a significant effect on restoration preferences. The survey on national parks in Finland revealed the restoration of peatlands and streams in national parks was widely accepted and important even though many of respondents were unaware of the previously restored areas or plans to be executed in the future. The respondents considered restoration actions more important than the increase of the number of trails and they would be willing to pay notably more to support conservation rather than park maintenance. The study on Nuuksio National Park showed that a large proportion of the respondents would visit Nuuksio irrespective whether more peatlands or streams were restored, or whether nearby forests were joined to the national park or not. Therefore, the restoration does not seem to have an impact on nature tourism in the short term. All in all, people tended to support restoration of peatlands and small water bodies and accepted the use of tax money to meet the restoration goals. Public opinion on restoration has seemed to stay relatively stable over the last years encouraging actions to be implemented all around Finland. Nevertheless, the large heterogeneity in survey responses underlines a need to consider the ‘winners’ and ‘losers’ of the restoration programs to increase the acceptance of restoration in society.
Keywords: citizen preferences; peatlands; ponds; restoration; small water bodies; streams; willingness to pay